Void reactivity aspect and fuel conversion potential of heavy water cooled thorium reactor. (20th July 2016) - Permana, Sidik; Waris, Abdul; Suud, Zaki; Sekimoto, Hiroshi
Summary: Design study on heavy water cooled thorium breeding reactor has been investigated by adopting a nuclear equilibrium state model. Conversion ratio, as an important index, has been evaluated to estimate the breeding capability of the reactors. Void reactivity coefficient has also been investigated to evaluate performance index of safety aspect, which is based on the criticality performance of the reactors during voided condition. In addition, moderator‐to‐fuel ratio has also been employed to analyze its effect to the required enrichment, conversion ratio, and void reactivity coefficient as well as different burnups and fuel pin diameter effects. Void reactivity coefficient indicates a criticality condition of the reactor when some coolants are lost. If the negative value of void reactivity is achieved, it means that the reactor has less reactivity condition as well as less power production when lost of coolant occurred. Higher fuel conversion capability, that more nuclear fuel are produced, those additional fuel productions can be used for next operation or for other reactors. The results show that higher fuel conversion ratio can be achieved for less moderator‐to‐fuel ratio because of the harder neutron spectrum effect, while it requires more fissile content of 233 U to maintain the reactor operation from fission reaction. Higher burnup gives less conversion ratio because some fissile materials are used to maintain longer reactor operation, and at the same time, it requires more initial required fissile 233 U for higher burnup. In addition, it requires less fissile 233 U for thicker fuel pin diameter, while its conversion ratio becomes higher, and void reactivity coefficient is more negative for thicker fuel pin diameter. The results also show that thorium utilization on heavy water cooled reactor gives all negative void reactivity values, which means that the system has a safety condition in terms of void reactivity condition. At the same time, it shows some feasible conditions for obtaining fuel breeding to increase the sustainability of nuclear fuel. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Based on the analyses, thorium utilization on heavy water cooled system shows that all obtained void reactivity are negative, which means the reactor gives in safety condition in term of void reactivity condition, and it shows some feasible conditions for obtaining breeding condition, which give the feasible design to increase the sustainability of nuclear fuel.